2020
DOI: 10.1017/s0033291720004298
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depressive symptoms and children's academic performance: sex differences in the mediating role of school experiences

Abstract: Background Maternal depressive symptoms (MDSs) are negatively associated with children's academic performance, with stronger effects sometimes reported in boys. However, few studies have tested the mechanisms of this association. We examined the mediating role of school engagement and peer victimization in this association and tested for sex differences. Methods Participants were 1173 families from a population-based longitudinal Canadian study. MDSs were self-reported annually using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Nevertheless, it is worth noting that maternal depression remained significantly associated with offspring cognitive outcomes after accounting for important covariates such as maternal anxiety and level of education. Furthermore, in the two studies which reported adjusted sex-specific associations (Ahun et al, 2020; Ng-Knight et al, 2018), sex differences remained after adjusting for covariates. It is therefore likely that our findings would hold after accounting for covariates.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Nevertheless, it is worth noting that maternal depression remained significantly associated with offspring cognitive outcomes after accounting for important covariates such as maternal anxiety and level of education. Furthermore, in the two studies which reported adjusted sex-specific associations (Ahun et al, 2020; Ng-Knight et al, 2018), sex differences remained after adjusting for covariates. It is therefore likely that our findings would hold after accounting for covariates.…”
Section: Discussionmentioning
confidence: 92%
“…In total, 12 articles from eight unique datasets met eligibility criteria and were included in the meta-analysis (Table 1). Studies were conducted in six countries: six in the UK (Hay et al, 2001; Hay, Pawlby, Waters, & Sharp, 2008; Murray et al, 2010; Murray, Hipwell, Hooper, Stein, & Cooper, 1996; Ng-Knight et al, 2018; Sharp et al, 1995), two in Canada (Ahun et al, 2020; Paquin et al, 2020), and one each in Australia (Cornish et al, 2005), the USA (Davies & Windle, 1997), South Africa (Donald et al, 2019), and Finland (Nolvi et al, 2018).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations